PENENTUAN AKTIVITAS ANTIOKSIDAN DAN TABIR SURYA DARI EKSTRAK BUNGA KENCANA UNGU (Ruellia tuberosa L) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Ginayanti Hadisoebroto; Syulastri Effendi; Jaqi Achmad Gifari; Hesty Nuur Hanifah (Jurnal Sabdariffarma: Jurnal Ilmiah Farmasi, 2026)
The purple kencana plant (Ruellia tuberosa L.) is a wild plant commonly found in the surrounding environment. The purple kencana contains secondary metabolite compounds such as alkaloids, phenolics, flavonoids, triterpenoids, and saponins. The flavonoid and phenolic compounds have the potential to act as antioxidants. Antioxidants can prevent the negative effects caused by UV radiation and provide protection against UV rays due to their conjugated double bonds, which can resonate when exposed to UV light, thus exhibiting photoprotective properties. This study aims to determine the sunscreen activity of the purple kencana flower extract by assessing antioxidant activity, as well as the Sun Protection Factor (SPF) and % Erythema Transmission using a UV-Vis Spectrophotometer. The research began with several stages, including plant determination, material collection, testing the characteristics of the simplicia, preparation of simplicia, and extraction of the purple kencana flower using 70% ethanol, followed by phytochemical screening, antioxidant activity testing using the DPPH method, and determining the SPF value and % Erythema Transmission. The results showed that the maceration of the purple kencana flower yielded a yield of 40%. Phytochemical screening of the purple kencana flower extract tested positive for alkaloids, flavonoids, phenols, saponins, and triterpenoids. The IC50 and IAA values for the purple kencana flower extract were 56.782 ppm and 0.881, respectively, which fall into the moderate antioxidant category. The SPF value obtained was 105.40, which falls into the ultra-protection category, indicating that it can be used as a sunblock based on the % erythema transmission value of 0.28%.